HUBUNGAN MEDIASI INTELLECTUAL CAPITAL DISCLOSEURE DENGAN GOOD CORPORATE GOVERNANCE DAN FIRM VALUE DALAM SEBUAH PENGARUH - Zuhroh, Nikmatu; Prasetyo, Eko; Antoro, Eko Wahyudi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
Due to their good value tendencies, companies indexed in LQ45 should be a reference for investors to invest in, but this is not always true. Among many influencing factors, GCG and ICD were unable to maintain their ranking in LQ45. The aim of this research is to evaluate the impact of GCG and ICD variables on company value directly and the impact of ICD variables on company value indirectly. Twenty-two sample companies were collected after the data was sorted. From 2017 to 2022, observations lasted for six years. This research uses SEM-AMOS. The research results show that GCG has a negative impact on ICD, but a positive impact on company value. In addition, ICD has a real and positive impact on ICD value and company value, but is not identified as an intervention variable.